Noninvasive monitoring of plant-based formulations on skin barrier properties in infants with dry skin and risk for atopic dermatitis - L. Lünnemann, MD; L. Ludriksone; M. Schario, ScD; S. Sawatzky; A. Stroux; U. Blume-Peytavi, MD; N. Garcia Bartels, MD (Wolters Kluwer, 2018)
Background: Dry skin and the associated impaired epidermal barrier function are postulated to constitute a major element in the development of atopic dermatitis. Objective: The aim of this study was to evaluate the effect of two plant-based formulations on the epidermal barrier function in a defined cohort of infants with a predisposition for atopic dermatitis. Methods: Over a period of 16 weeks, 25 infants who were ages 3 to 12 months and had an atopic predisposition and dry skin received two emollients that contained pressed juice of the ice plant. The infants received both cream and lotion on the forearm, only cream on the face, and only lotion on the leg. Stratum corneum hydration (SCH), transepidermal water loss (TEWL), skin surface pH, and sebum were assessed on the infants' forehead, leg, and forearm. The Scoring Atopic Dermatitis (SCORAD) index was used for the clinical assessment. Results: SCH significantly increased in all body regions that were assessed. The forearm and leg revealed stable levels of pH and TEWL, but a decline in pH (week 16) and TEWL (week 4) was noted on the forehead. At week 16, sebum levels were lower on the forehead compared with those at baseline. SCORAD scores improved significantly during the study. Conclusion: A daily application of both emollients was associated with increased SCH levels and a stable course of TEWL, pH, and sebum on the forehead except for the forehead when compared with the forearm and leg. Clinically, improved SCORAD scores were noted.